2008
DOI: 10.1111/j.1365-2753.2007.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐centredness, self‐rated health, and patient empowerment: should providers spend more time communicating with their patients?

Abstract: Reliance solely on patient-centred communication to promote empowerment may be insufficient as well as costly. Instead, improved one-to-one communication between patients and providers should be reserved for clinically complex and urgent situations. For other health matters, referral of patients to community health promotion and education programmes should be considered because this may offer a lower-cost approach to empowerment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 17 publications
2
36
0
5
Order By: Relevance
“…A literature review points out that the empowerment associated with planned visits and care coordination improves outcomes of COPD treatment. 41 Rohrer et al 42 highlight the adoption of a direct measure of empowerment, that is, the patients' own perception of being in control of their own health. Moving in this direction, our systematic review revealed the patients control of their health state.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review points out that the empowerment associated with planned visits and care coordination improves outcomes of COPD treatment. 41 Rohrer et al 42 highlight the adoption of a direct measure of empowerment, that is, the patients' own perception of being in control of their own health. Moving in this direction, our systematic review revealed the patients control of their health state.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, however, there appears to be much variance between and within (older) patients concerning their wish to participate in medical decision-making: not all patients are equally willing to do so (Bastiaens et al, 2007;Brody, 1980;Frosch & Kaplan, 1999;Roberts, 1999). Generally, it was seen that if patients were more involved in their own care, they showed better health behaviours (Hochhalter, Song, Rush, Sklar, & Stevens, 2010) and improvement in control of chronic diseases (Rohrer et al, 2008). In the literature these behaviours are often referred to as self-management (Lorig & Holman, 2003).…”
Section: Literature Overviewmentioning
confidence: 99%
“…In relation to control in the health care setting specifically, authors often discussed the role of the doctor-patient relationship, by describing phenomena such as shared decision-making (Brody, 1980;Frosch & Kaplan, 1999), and patient-centred approaches in the medical practice (Mead & Bower, 2000;Rohrer, Wilshusen, Adamson, & Merry, 2008). Brody (1980) argued that whenever people are ill, less self-reliant, and need to depend on the doctor's decisions, this may undermine their sense of control and self-esteem, as well as their sense of dignity, which shows the importance of patient involvement in the care process.…”
Section: Literature Overviewmentioning
confidence: 99%
“…choice about what? ), but research in this area has used diverse definitions and measures, with 'choice' often embedded within broader concepts such as 'patient-centred care', 'patient empowerment', 'patient involvement' or 'shared decision-making' [8][9][10][11]. Moreover, despite the widespread claim -within the NHS and beyond -that good practice entails a more 'shared' (as opposed to a more 'paternalist') approach, the empirical literature offers far less consensus.…”
Section: Introduction (Revised)mentioning
confidence: 99%